ДОСЛІДЖЕННЯ АЛГОРИТМІВ АДАПТИВНОЇ ПРОТИАВАРІЙНОЇ АВТОМАТИКИ ПІВДЕННОГО РЕГІОНУ ОЕС УКРАЇНИ - Стогній, Б.С.; Авраменко, В.М.; Сопель, М.Ф.; Прихно, В.Л. (Інститут електродинаміки НАН України, Київ, 2014)
An adaptive emergency control automatics is proposed for maintenance of power systems stability, which is based on microprocessors and controls the stability margin of the current state and determines the control actions, which are necessary to meet normative requirements as to the active power in the cross sections and so to the voltage at the centers of consumption. It is shown that the soft and hard ware complex system "Rehina - F" on its technical features and functionality is not worse the best world standards. Demands to MP emergency control with centralized formation of dosage control actions is formed. References 7, tables 4, figure 1.